2020
DOI: 10.1183/13993003.02208-2019
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C to pregnant smokers persistently improves infant airway function to 12 months of age: a randomised trial

Abstract: BackgroundVitamin C (500 mg·day−1) supplementation for pregnant smokers has been reported to increase newborn pulmonary function and infant forced expiratory flows (FEFs) at 3 months of age. Its effect on airway function through 12 months of age has not been reported.ObjectiveTo assess whether vitamin C supplementation to pregnant smokers is associated with a sustained increased airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
(49 reference statements)
3
26
0
1
Order By: Relevance
“…Two separate randomized trials have shown that vitamin C supplementation to pregnant women unable to quit smoking improved the lung function of their offspring through 12 months of age. 32,33,68 Interventions to decrease in utero smoke exposure or mitigate its effects will likely improve airway function trajectories in both preterm and term infants particularly with the increased use of electroniccigarettes. 69 In the postnatal period, a randomized trial of premature infants has revealed that extending treatment with CPAP until 34 weeks PMA significantly increased lung volumes as measured by FRC at discharge, 27 a finding that suggests one postnatal pathway to improve lung trajectories.…”
Section: Can Early Lung Function Be Maximized and Lung Trajectories Be Positively Redirected Toward Higher Maximum Function?mentioning
confidence: 99%
“…Two separate randomized trials have shown that vitamin C supplementation to pregnant women unable to quit smoking improved the lung function of their offspring through 12 months of age. 32,33,68 Interventions to decrease in utero smoke exposure or mitigate its effects will likely improve airway function trajectories in both preterm and term infants particularly with the increased use of electroniccigarettes. 69 In the postnatal period, a randomized trial of premature infants has revealed that extending treatment with CPAP until 34 weeks PMA significantly increased lung volumes as measured by FRC at discharge, 27 a finding that suggests one postnatal pathway to improve lung trajectories.…”
Section: Can Early Lung Function Be Maximized and Lung Trajectories Be Positively Redirected Toward Higher Maximum Function?mentioning
confidence: 99%
“…A second larger RCT randomized 251 pregnant women between 13 and 23 weeks gestation who smoked to either placebo or 500 mg oral vitamin C daily. 51 Infants in the vitamin C group were found to have improved forced expiratory flows over the first year. Continued follow-up on these populations are ongoing.…”
Section: Prevention Of Tobacco Use or The Consequences Of Usementioning
confidence: 95%
“…Algunos estudios han señalado que mejorar la situación de la vitamina C en las gestantes fumadoras puede ayudar a antagonizar el daño inducido por la nicotina. Concretamente, en un ensayo aleatorizado y controlado con placebo, al suministrar vitamina C a mujeres embarazadas fumadoras se observó una mejora, estadísticamente significativa, de la función pulmonar del descendiente a los 3 meses (24) y 12 meses de edad (25).…”
Section: Sanitarios Para Los Fumadoresunclassified